Aloe vera vs. poly(ethylene)glycol-based synthesis and relative catalytic activity investigations of ZnO nanorods in thermal decomposition of potassium perchlorate. (4th May 2017) - Patel, V. K.; Sundriyal, P.; Bhattacharya, S.
ABSTRACT: The green synthesis approach using ecofriendly biological precursors has gained world-wide popularity, reputation and recognition in the synthesis of several inorganic nanomaterials. This work demonstrates that a proper selection of biological precursor from the sustainable natural resources can effectively replace the commercial surfactant for fabrication of nanomaterials. Through this work, the green biotemplate Aloe vera plant extract has emerged as a better substitute of industrial surfactant poly(ethylene)glycol of molecular weight 8000 (PEG8000) in synthesis of ZnO nanorods using a simple sonoemulsion route. The colloidal growth of ZnO nanorods in PEG8000/Aloe vera -assisted sonoemulsion route has been elaborated in the context of relative supremacy of ultrasonic-assisted self-aggregation rate with steric-hindrance effect imposed by PEG8000/Aloe vera . The relative catalytic activity of PEG8000/Aloe vera synthesized ZnO nanorods, Co3 O4 nanobelts and CuO nanorods in thermal decomposition of potassium perchlorate has been studied by thermo-gravimetric analysis and differential thermal analysis of pure potassium perchlorate and its mixture with nanoscale ZnO/Co3O4/CuO by 2% weight. The ZnO nanorods formulated through Aloe vera route demonstrated higher catalytic activity than that of ZnO nanorods prepared through PEG8000 route. The relative order of catalytic effect of nanoscale metal oxides in thermal decomposition of potassium perchlorate was found in descending order as CuO nanorods > Co3 O4 nanobelts > ZnO nanorods.